Design of trust identification system for cloud services. (25th August 2021) - Devi, R.; Shanmugalakshmi, R.
Cloud computing is merging into every aspect of our information exchange including our personal information, business environment and other environments along with numerous security and trust challenges. With rapidly developing cloud utilisation, the range of security issues and trust challenges also increases exponentially. Hence an efficient trust identification system (TIS) is needed to identify the region of trusted cloud service providers (CSPs) for a particular service. In this paper, a novel trust identification technique is proposed based on linear programming using objective functions which can smartly spot the region of trust from the CSP pool. In this system, the cluster of trusted CSP is defined and the remaining CSPs are not recommended to the cloud customer (CC). The internet architecture is a wide area network with interoperability, scalability and durability. The analysis of the proposed system proves to be efficient in terms of accuracy and time complexity.